All‐Electrical Programmable Domain‐Wall Spin Logic‐In‐Memory Device. (7th July 2022) - Wang, Weiyang; Sheng, Yu; Zheng, Yuanhui; Ji, Yang; Wang, Kaiyou
Abstract: Control of spins by spin–orbit torque brings novel strategies to design spintronic devices with potentially high impact in data storage and logic‐in‐memory computing architectures. Although various attempts have been proposed to avoid the participation of magnetic field during magnetization switching for realizing multifunctional spin logic devices, simpler and more feasible approaches are still strongly desired. Here, field‐free current‐induced magnetization switching is achieved through magnetic domain wall (DW) motion in a dual‐channels device, where the chiral Néel DW is stabilized by the strong Dzyaloshinskii–Moriya interaction in Pt/Co/Ru asymmetric structure. By electrically programming the initial magnetization states of the device with two opposite switching modes, four Boolean logic gates of AND, NAND, OR, and NOR are demonstrated. This work demonstrates that ingenious geometry design can be important for developing the spin logic devices and in‐memory computing architectures. Abstract : All‐electrical programmable domain‐wall spin logic‐in‐memory device with dual conductive channels is demonstrated. Field‐free current‐induced magnetization switching is achieved through current‐driven domain wall reciprocating motion. Furthermore, four logic gates of AND, OR, NAND, and NOR are demonstrated in a single device, which is encoded in switching chirality (clockwise/anticlockwise) and initial magnetization state (up/down).